Towards a sustainable legacy: integrating net-zero targets into mine rehabilitation and closure planning - Boshrouyeh, B; Amari, S; Hattingh, R (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
In alignment with the goals of achieving net-zero emissions and fostering a circular economy, this study explores innovative approaches for the relinquishment of lands following mine closure. It emphasises the integration of renewable energy sources, the cultivation of biofuels and the implementation of innovative natural battery storage technologies. By analysing a series of global case studies that highlight inventive practices for post-mining land use, this research outlines critical selection criteria and strategic planning recommendations to assist mine closure planners and mine operators in creating sustainable post-mining environments. To ensure a practical and informed approach, the study utilises a risk-based methodology to develop the selection criteria. Following this, a comprehensive strengths, weaknesses, opportunities and threats (SWOT) analysis is undertaken to systematically evaluate the strengths, weaknesses, opportunities and threats associated with each of these technologies for post-mining closure applications. This study maps a path for making mine closures a positive transition with sustainable assets and contributes to the broader journey towards environmental sustainability and circularity.
Keywords: mine closure